PROSES PEMBUATAN BRACKETBRAKE PEDAL STOPPER TYPE SU2ID MENGGUNAKAN MESIN STAMPING PRESS - Faqih, Reynanda Maulana Yusuf; Koswara, Engkos (Universitas Majalengka, 2024)
AbstractPersada Selaras Indonesia is a company operating in the field of stamping and die sheet metal in Majalengka Regency. One of the products produced at PT. Persada Selaras Indonesia is part of the Brake Pedal Stopper Bracket. In the process of making Brake Pedal Stopper Bracket Parts using SAPH-440 material using a Press Stamping Machine with a capacity of 110 Tons through the Dies selection process for the Blanking, Bending (1 + 2), and Pierching processes. Researchers used the observation method to determine the process of the Brake Pedal Stopper Bracket Part. The Brake Pedal Stopper Bracket Part is one of the components contained in the brake pedal of the Hyundai Creta vehicle which is produced at PT. Persada Aligned Indonesia. The process of making Brake Pedal Stopper Bracket Parts is divided into several parts, namely the Planing process, Shearing, Blanking Process, Bending Process (1 + 2), Pierching Process, and Quality Control Process. Keywords : SAPH-440, Press Stamping Process, Part Bracket Brake Pedal Stopper